A Novel Technology for Removal of Calcium in Magnesite by Flotation and Leaching - Zhu Yangge; Hu Xiaoxing; Zheng Guibing (International Mineral Processing Congress, 2018)
"Because of the similar crystal structure and surface properties, it is very difficult to realize the efficient separation of magnesite and dolomite by flotation, which is the main reason restricting the utilization of magnesite resources with dolomite symbiotic. To deal with a magnesite resources with high content of calcium impurity in northwest China, a novel decalcification technology by combining flotation with leaching is proposed in this paper. In flotation process, a novel flotation collector with good efficiency and low temperature resistance was developed, and the depression effect of sodium hexametaphosphate was investigated. In leaching process, the leaching rate difference of calcium and magnesium was observed. By industrial test, from the magnesite ore with MgO content of 43.96%,the grade and recovery of obtained concentrate ( calculated by MgO) are 47.28% and 67.68% respectively, at the same time, CaO content decreases from 3.91% to 0.30%, which means that more than 95% of CaO impurity is removed.INTRODUCTIONMagnesite is one of the main raw materials for the production of refractory materials, and it is widely used in metallurgy, chemicals, ceramic, construction and other industries. China is the most important supplier of highquality magnesite resources, accounting for about 60-70% of the world's identified supply of magnesite products is provide by China (Jewell, 2014). In recent years, high-quality magnesite ores can be directly used are going to run out in China, and the utilization of magnesite resources with high impurity content have drawn more attention.The main purpose of purification for magnesite is to remove SiO2 and CaO impurities which affects the strength of the refractory material. Flotation is the commonly used method to remove impurities in magnesite ore. Reverse flotation with cationic collector is usually adopted to remove silicon containing impurities, and a great deal of literature has been reported (Santana A. N. and Peres A. E. C., 2001; Wang and Sun, 2008; Zhu et al, 2014; Wu et al, 2015; Ivan B. et al, 2017). But when the major gangue component is dolomite, it is very difficult to realize the efficient separation due to the similar crystal structure and surface properties between magnesite and dolomite. To solve this problem, researches have studied the surface properties of magnesite and dolomite, such as wettability, electrical property, solubility and solution chemistry (Nermin and Nurgul, 2006; Nermin 2006; Ozbek and Abali, 1999; Lacin et al, 2005; Bayrak et al, 2006; Bakan et al, 2006; Chen G. and Tao D., 2004), but the commonly studied direct flotation using oleic acid as collector is still hard to receive an ideal effect."